(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The ecological crisis of the modern world calls for a profound reassessment of the relationship between humans and nature. Islam—being a morally and spiritually comprehensive system—offers a balanced worldview that integrates ecological responsibility with faith and practice. In the Qur’an, nature is not portrayed as a mere resource created for human exploitation; rather, it is described as a divine sign (ayah) that reflects Allah’s wisdom, order, and mercy. This article analyzes the approach to environmental ethics in the Qur’an, with particular focus on the concepts of human stewardship (khilafah), balance (mizan), and moderation (wasatiyyah). The study also explores prophetic traditions promoting ecological consciousness and reviews modern Islamic environmental movements. By linking theological foundations with contemporary ecological necessities, the research highlights Islam’s potential contribution to global discussions on sustainability and environmental justice.